Peranan Psikologi Guru dalam Pendidikan untuk Pencegahan Perundungan Siswa Sekolah Dasar - Imas Masitoh; Miftah Nurul Maarif; Alfiyatun Alfiyatun; Cici Rasmanah; Ujang Anwar Fauzi; Desi Sri Sulistia; Jamiludin R (Journal Innovation In Education, 2024)
Bullying is a term for acts of violence or bullying committed by stronger parties both in terms of age, strength, power to the weak. Forms of bullying behavior are physical bullying, verbal bullying and mental / psychological bullying that can have a negative impact on the victim, such as bruises, wounds, pain, timidity, etc. and for the long term namely disruption of psychological conditions and poor social adjustment. The role of educational psychologyCounselors have an important role in preventing and overcoming bullying in schools, for that efficient and comprehensive services are needed to all students by using various skills and media that can help the performance of educational psychology in dealing with bullying.